Penerapan Literasi Di Desa Wisata Cikolelet Melalui Perpustakaan Keliling Dan Taman Bacaan Masyarakat - Ida Nuraida (ABDIKARYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2019)
ABSTRACT Literacy is the one of reading and writing skills capabilty. The Information of literacy as the competion have to give the information to society. The one Literacy implementation at the cikolelet vilages tourism have the purpose for critical thinking capabilty. The devlopment of Information and communication is veryhight, but did not always took society solution. The problem condition is the internet information linked gate and its make the user confuse. The libracy target is to give the socialization about education information and the library proggrame applied to the society are mobile library and library field. The other side, the litaracy implementation in Cikolelet vilage through mobile library and library field for society become the solution to looking for the information and become the inovation to icreasing the literacy society.